Il rapporto oggettuale. Investimento e introiezione - Fagioli, Massimo (Il sogno della farfalla, 2022)
The article, which was already published in 1974 as part of Two essays of dynamic psychology, represents the introduction to the seminar held by Massimo Fagioli at the 11th Scientific Congress of the Italian Psychoanalytic Society (Bologna, 10-11 June 1972). Through the exposition of a clinical case, the author analyzes some aspects of the “objectual relationship”: on one side the ambivalent pulsion of the object’s investment and on the other introjection and projection. Consequently, this led to the proposition of a psychotherapeutic praxis, based on the concept of interpretation and psychotherapeutic frustration-interest which is founded on the underlying principle of the existence of the patient’s original Self.